Neonatal Cord Care Practices among Mothers and Caregivers in the Volta Region of Ghana - Sybil S. Opoku Asiedu, MPH; Nana Abena Ansah Apatu, BSc; Rosemond Tetteh, BSc; Abraham Hodgson, MBChB, MPH, PhD (Global Health and Education Projects, Inc., 2019)
Background: The umbilical cord is a major route of infection among newborns. In Ghana, infections among neonates accounts for majority of under-five deaths. This study sought to investigate what mothers apply to the umbilical cord of their newborns and what motivates them to put such applications on the cord. Methods: This was a descriptive cross-sectional study of neonatal cord care practices among mothers and caregivers in the Nkwanta South District of the Volta region of Ghana. Quantitative and qualitative methods were used. Results: Majority of the mothers/caregivers used substances that have not been recommended for umbilical cord dressing (64.3%). Factors such as level of education [χ2=8.2, p=0.02], place of delivery [χ2 = 40.1, p<0.001], relationship with whoever has made a recommendation for a particular dressing to be used [χ2=95.2, p<0.001] and number of days it takes the umbilical cord to fall off [χ2=6.2, p=0.05] were found to influence the type of dressing used on the umbilical cord. Conclusion and Global Health Implications: In order to reduce the number of neonates who die due to avoidable cord-related infections, the type of substances used on the umbilical cord should be approved substances. Health education particularly on neonatal cord care targeting community members and health care providers at the lower levels of the healthcare delivery system should be intensified. Key words: • Umbilical cord • Neonates • Newborns • Rural • Dressing • Infections • Ghana   Copyright © 2019 Asiedu et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.